2014
DOI: 10.7821/naer.3.1.26-33
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and natural selection: learning by playing and reflecting

Abstract: Scientific literacy is more than the simple reproduction of traditional school science knowledge and requires a set of skills, among them identifying scientific issues, explaining phenomena scientifically and using scientific evidence. Several studies have indicated that playing computer games in the classroom can support the development of studentsʼ conceptual understanding about scientific phenomena and theories. Our paper presents a research study where the role of the video game Spore as a learning tool wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
(20 reference statements)
0
9
0
1
Order By: Relevance
“…This caused them to carry out more operations and to be more careful in achieving the correct answer. Herrero et al (2014) consider educational and learning activities for conceptual subjects in using the method of presentation of the important features of the concepts, examples and non-examples and using conceptual map in order to show the relationship between the concepts and the types and elements of the concept by using pictures in learning the concept. Kapp (2012) states that learners, in order to learn concepts, must know the important features of concepts in order to be able to recognize and classify examples and non-examples of concepts; he suggests that in order to learn concepts in educational games, it is better to use the mechanics of matching, classifying, and experiencing the concept itself.…”
Section: Achievements and Evaluation Of Game Workhop Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This caused them to carry out more operations and to be more careful in achieving the correct answer. Herrero et al (2014) consider educational and learning activities for conceptual subjects in using the method of presentation of the important features of the concepts, examples and non-examples and using conceptual map in order to show the relationship between the concepts and the types and elements of the concept by using pictures in learning the concept. Kapp (2012) states that learners, in order to learn concepts, must know the important features of concepts in order to be able to recognize and classify examples and non-examples of concepts; he suggests that in order to learn concepts in educational games, it is better to use the mechanics of matching, classifying, and experiencing the concept itself.…”
Section: Achievements and Evaluation Of Game Workhop Resultsmentioning
confidence: 99%
“…Games are used in order for training and changing of attitudes (Joyce, Weil, Calhoun, 2004). Many studies have shown that playing games can be used in order to teach students' conceptual understanding of theories such as the theory of natural selection (Herrero et al, 2014). Educational game is a planned, competitive, and purposeful activity which includes a set of roles and designs.…”
Section: Introductionmentioning
confidence: 99%
“…Task and project work (Pacte, 2000) is a suitable methodology in the inclusive classroom alongside ICT in all its dimensions: games (Herrero et al, 2014), curricular proposals, etc.…”
Section: Discussionmentioning
confidence: 99%
“…makes children learn that the animal is an affectionate, valuable beloved being" (Signes, 2010, p.4). That occurs in a family context, but it can also be the result of an institutional activity in which learning is not only at an individual level, but at a collective one (Iglesias & Astorga, 2014), with similar methods to those of gaming, regarding methodology, human relations and the processes of collective communication (Herrero et al 2014). …”
Section: Learning Through Observationmentioning
confidence: 99%